Analisis Faktor Faktor Yang Mempengaruhi Investasi Asing Langsung Di 5 Negara Asean Data Panel 2010-2021 - Dena Ayu Aviantih (Jurnal Ilmiah Wahana Pendidikan, 2023)
Foreign Investment is one of the most important things to improve the country's economy. One of them is a country in Southeast Asia that is part of ASEAN. ASEAN countries have an increasing number of foreign investment every year. This study aims to determine the factors that influence foreign investment in 5 ASEAN countries, namely the Philippines, Indonesia, Malaysia, Singapore and Thailand. They are the countries forming the ASEAN organization that are expected to know the purpose of this research. This analysis uses the panel data analysis method because it uses combined data, namely cross sections and time series for 5 countries from 2010-2021. Using domestic product variables, inflation rates, and interest rates. The results show that there is an effect of gross domestic product and interest rates on foreign direct investment, but the inflation variable has no effect on foreign direct investment.